The Effect of Ethylene Gas Exposure of Tomatoes (Solanum lycopersicum) on the Morphological Growth of Green Beans (Vigna radiata) - Beatrix Putri Septianingrum; Dinda Khairurohmah; Intan Kurniyati (Jurnal Biologi Tropis, 2026)
Ethylene is one of the natural growth hormones produced by fruits such as tomatoes, and is known to have an important role in regulating various plant physiological processes. This research was conducted to examine the effect of natural ethylene gas from tomatoes on the early growth of green bean plants (Vigna radiata). The research used a simple experimental method with two treatment groups, namely the group of plants exposed to ethylene gas from tomatoes and the control group without ethylene exposure. The observed parameters include stem height and root length in a certain period of time. Observation results show that exposure to ethylene affects the growth of green bean plants, especially in increasing the height of the stem which is more significant than control plants. Based on the findings, it can be concluded that ethylene gas produced naturally by tomatoes has the potential to accelerate the early growth of green bean plants.